PAX8 Distinguishes Diffuse Large B-Cell Lymphoma Mimicking Sarcoma - Michelle S. Hirsch; Alessandra F. Nascimento (Case Reports in Pathology)
PAX8 is important for embryogenesis of the thyroid, Müllerian system, and upper urinary/renal tract, and expression of PAX8 has been described in carcinomas from each of these sites. The sensitivity and specificity of the polyclonal PAX8 antibody in a large cohort of epithelial tumors as well as lymphomas have been previously determined, the latter because polyclonal PAX8 is known to be immunoreactive in nonneoplastic B-cell lymphocytes which are often used as the positive internal control for immunohistochemistry. In this case report, PAX8 was a diagnostic clue for revising a previous diagnosis of unclassified high grade sarcoma to diffuse large B-cell lymphoma. This case report demonstrates a pitfall for PAX8 immunoreactivity and acts as a reminder that lymphoma should be included in the differential diagnosis of a PAX8 positive, epithelial cell marker negative tumor of unknown primary origin.